Evaluation of femoral head bone quality by Hounsfield units: A predictor of implant failure for intertrochanteric fractures after intramedullary nail fixation - Fan, Jixing; Lv, Yang; Xu, Xiangyu; Zhou, Fang; Zhang, Zhishan; Tian, Yun; Ji, Hongquan; Guo, Yan; Yang, Zhongwei; Hou, Guojin (Frontiers in Surgery, 2023)
Purpose The aim of present study is to evaluate the femoral head bone quality by Hounsfield units and its relationship to the occurrence of implant failure for intertrochanteric fractures after intramedullary nail fixation. Methods This retrospective study assessed 160 intertrochanteric fractures treated with intramedullary fixation. Patients with and without implant failure were divided into failure and control groups, respectively. The demographic information, femoral head Hounsfield unit (HU) value, the reduction quality, status of posteromedial support and position of the screw/blade were collected and compared. The logistic regression analyses were performed to evaluate risk factors of implant failure in intertrochanteric fractures after intramedullary nail fixation. Results Of the patients, 15 (9.38%) suffered from implant failure after intramedullary fixation. The mean HU value of femoral head was much lower in the failure group than the control group (133.25 ± 34.10 vs. 166.12 ± 42.68, p = 0.004). And the univariate analyses showed that A3 fracture and poor reduction quality were associated with implant failure (p < 0.05). After adjustment for confounding variables, the multivariable logistic regression analyzes showed that femoral head HU value (odds ratio [OR], 0.972; 95% CI, 0.952–0.993; p = 0.008) and poor reduction quality (OR, 7.614; 95% CI, 1.390–41.717; p = 0.019) were independent influencing factors for implant failure. Conclusion The femoral head HU value was significantly correlated with the incidence of implant failure and can be used as an independent factor to predict implant failure for intertrochanteric fractures after intramedullary fixation.